Risk Management in Project Financing - Thakkar, Kinnarry (SFIMAR Research Review, 2016)
The paper intends to explain the contemporary methods of raising loan for financing infrastructure projects and the types of risk involved in financing the projects. Project financing is an innovative technique of raising finance for long-term infrastructure and industrial projects. It is generally used for high profile projects based upon complex financial structure. Unlike the conventional method of raising finance, project financing involves understanding the rationale for project financing, how to prepare the financial plan, assess the risks, design the financing mix, and raise the funds. In traditional financing structure the non-payment risk associated with the buyer is considered significant. However in project financing it becomes imperative to act creatively to minimize the risk embodied in the project. In project financing the financier usually has little or no recourse to the non-project assets of the borrower or the sponsors. In such case repayment of loan can be done only when the project becomes operational. If the project fails to generate cosh-flows as per the expectations the financiers are likely to lose substantial amount of money. Consequently due to highly specialized and illiquid nature of such assets they have low safe value. Each project g ives rise to unique set of risks posing unique challenges in risk management. The financiers need to mitigate the risk in order to ensure that the project will be a success. The process of risk mitigation involves identification, analysis, allocation and management of risks at the constructional and operational level. Effective management is a key for successful project financing.